The use of the internet in media education - Özad, Bahire Efe; Kuto?lu, Ülfet (My University, 2010)
The Internet has become the main information and data provider since its appearance at the end of the 20th century. Currently, all over the world, universities, as the main generators and consumers of information, stand at the top of the privileged organizations that have access to the Internet. Hence, being a tertiary student means not only having easy, quick, and cheap, even in most places free, access, but also being bombarded with information. This led to a considerable body of research into the attitudes and habits of using the Internet by the university students in the world as well as Turkey and North Cyprus. The present study sets out to explore the attitudes of students, studying at the Faculty of Communication and Media Studies, Eastern Mediterranean University, towards the use of the Internet as a source/tool for obtaining information for their course work, communication and otherwise. Data have been collected through a questionnaire designed in two parts: the first part seeks to collect information about the participants' genders, ages, departments, the year of studies, and their practice related to the use of the Internet and the second part related to their attitudes towards the use of various aspects of the Internet. The results indicate that students hold a positive attitude towards the use of the Internet both for academic and communication purposes. The Internet is considered as the best and fastest information provider and is necessary for tertiary students. Both the lecturers and students should have web-sites. They are, however, undecided about the trustworthiness of the information they find on the web or printing everything they find on it before reading. Furthermore, they are undecided about the fact that the Internet makes them feel lonely. The students also stated that they are undecided about online shopping, online banking, playing games on the Internet rather than doing any other hobby. © The Turkish Online Journal of Educational Technology.
Keywords: Internet; Students' attitudes; Tertiary media education